(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents part of a doctoral research in Performing Arts with children in Basic Education in contexts of precariousness in the Federal District, Brazil. The objective is to recognize and analyze children’s narrative performances with a view toward an anti-racist pedagogy. The notion of bodily states is introduced through an artistic-performative practice committed to addressing the structural racisms faced by students. The proposed bodily states are named: aerial body; bonding body; present body; and manifest body. These bodily states are presented as anti-racist pedagogical possibilities.